The aesthetics of Mesopotamian furniture and its reflections in contemporary furniture design (Al-Academy, 2024)
There is no doubt that furniture is a representation of human concepts, values, requirements and needs, and despite the modernization and contemporaneity that has accompanied furniture design from the era of Mesopotamia to the present day in order to secure the needs of the user and the efficiency of the design, therefore the two researchers took the importance of the reflections of Mesopotamian furniture in contemporary furniture design due to its aesthetics and shapes. Therefore, the problem of the research lies in the following question: - Is it possible to employ the aesthetics of Mesopotamian furniture designs with its symbols and shapes in contemporary furniture design to ensure the achievement of cultural communication between the past and the present and consider it as a design basis? The research also aimed to reach the creative ability of the Mesopotamian design principles and consider them a design foundation that achieves aesthetic aspects in contemporary furniture design. The two researchers also reviewed the theoretical framework, which included an introduction to the arts of the Mesopotamian civilization, the design principles of Mesopotamian furniture, and the Mesopotamian aesthetic influences in contemporary furniture design. As for the keywords lost, they were specified as (aesthetics, Mesopotamia, contemporary) and the most important results and conclusions were reached, the most important of which was (that the uses of Mesopotamian furniture, with the qualities of flexibility and shaping in furniture design, are consistent with the characteristics of furniture design thought for the post-modern period, The combination of past and present has characteristics and features that can be employed in industrial design in general and contemporary furniture design in particular